Supramolecular Pressure‐Sensitive Adhesives with Rapid, Strong, Water‐Resistant, and Underwater Adhesion - Jialing Li; Yunfei Zhang; Qiao Zhang; Changyong Cai; Fenfang Li; Shengyi Dong (Advanced Materials Interfaces, 2023)
Abstract Supramolecular polymers are materials that exhibit a range of functionalities and thus find wide applicability. In this study, two natural low‐molecular‐weight compounds, thioctic acid (TA) and phytic acid (PA), are used to fabricate polymeric supramolecular structures. The coexistence of dynamically covalently linked poly(TA) and hydrogen bond linked poly(PA) moieties result in copolymeric materials with different dynamic features. The obtained poly(TA‐PA)s show rapid and strong adhesion on a variety of natural and artificial surfaces, with high 180° peeling, lap‐shear, and pull‐off strengths over wide temperature (−18 °C to 60 °C) and humidity (20−99%) ranges. The poly(TA‐PA)s also display good stability and adhesion in the presence of water, even show stable and long‐lasting underwater adhesion. Hence, the synthesized poly(TA‐PA)s, which have high water resistance, are suitable for use as sealing materials in various applications, thus highlighting the applicability of supramolecular polymer materials in underwater surface coatings and adhesion.